Immigrants from Balkan countries in Greece: local and transnational processes of incorporation in Thessaloniki - Panos Hatziprokopiou (Belgeo)
This paper examines three different contexts of incorporation of immigrants from Albania and Bulgaria in the Greek city of Thessaloniki: (a) at the socio-political level, focusing on the polity’s and civil-society’s “responses” to immigration; (b) at the socio-economic level, discussing the labour market integration of immigrants in Thessaloniki; (c) at the socio-spatial level, regarding the relation between immigration and urban dynamics. Within the transnational space that is being formed in the Balkans, Thessaloniki seems to have become a new home for migrants from Balkan countries. However, immigrants’ lives in the city are determined by the socio-spatial and economic urban dynamics, which are subject to international forces of restructuring and change.